ANALISIS KINERJA LALU LINTAS PADA RUAS JALAN RAYA NEGARA SUMBAR - RIAU SEGMEN 2 KABUPATEN LIMA PULUH KOTA - Alfajri, Alfajri; Yermadona, Helga; Endri, Endri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The Tanjung Pati area is crossed by the West Sumatra-Riau State Highway segment 2 with the function of an arterial road which is a busy access for vehicles to and from Riau Province. The research aims to analyze traffic volume, side obstacles, traffic performance, and proposed problem solving. Results of analysis of existing conditions Traffic Volume 1590.6 pcu/hour, Road Capacity 2017 pcu/hour, Degree of Saturation 0.79, Speed 30 km/hour, Service Level